Safety and effectiveness of midazolam for cirrhotic patients undergoing endoscopic variceal ligation - Jo, Hee Bum; Lee, Jun Kyu; Jang, Dong Kee; Kang, Hyoun Woo; Kim, Jae Hak; Lim, Yun Jeong; Koh, Moon-Soo; Lee, Jin Ho (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Endoscopic variceal ligation (EVL) is an established treatment for esophageal variceal bleeding. Midazolam (MDZ) is most commonly used for sedation during endoscopic procedures. However, adverse events (AEs) may occur more frequently in patients with cirrhosis due to altered MDZ metabolism. Materials and Methods: We retrospectively reviewed the records of 325 patients with cirrhosis who received EVL. Results: No significant differences were found in treatment outcome and procedure time among 151 patients in the MDZ group and 169 patients in the non-MDZ group. Desaturation (23.2% vs. 7.7%, p<0.01), bradycardia (22.5% vs. 17.2%, p=0.03), and hepatic encephalopathy (HE) (6.6% vs. 0.6%, p<0.01) were more common in the MDZ group than in the non-MDZ group. Logistic regression analyses revealed that an Eastern Cooperative Oncology Group (ECOG) score of ≥2 (p<0.01) and the use of MDZ (p<0.01) were associated with the development of overall AEs. An ECOG score of ≥2 (p=0.01), high serum creatinine level (p=0.02), and the use of MDZ (p<0.01) were significant risk factors for HE. Conclusion: Extreme caution should be taken when sedating patients with cirrhosis receiving EVL due to the AEs associated with the use of MDZ. Cite this article as: Jo HB, Lee JK, Jang DK, et al. Safety and effectiveness of midazolam for cirrhotic patients undergoing endoscopic variceal ligation. Turk J Gastroenterol 2018; 29: 448-55.